A state of the art overview of carbon-based composites applications for detecting and eliminating pharmaceuticals containing wastewater. (February 2022) - Nabgan, Walid; Jalil, Aishah Abdul; Nabgan, Bahador; Ikram, Muhammad; Ali, Mohamad Wijayanuddin; Ankit kumar,; Lakshminarayana, Parashuram
Abstract: The growing prevalence of new toxins in the environment continues to cause widespread concerns. Pharmaceuticals, organic pollutants, heavy metal ions, endocrine-disrupting substances, microorganisms, and others are examples of persistent organic chemicals whose effects are unknown because they have recently entered the environment and are displaying up in wastewater treatment facilities. Pharmaceutical pollutants in discharged wastewater have become a danger to animals, marine species, humans, and the environment. Although their presence in drinking water has generated significant concerns, little is known about their destiny and environmental effects. As a result, there is a rising need for selective, sensitive, quick, easy-to-handle, and low-cost early monitoring detection systems. This study aims to deliver an overview of a low-cost carbon-based composite to detect and remove pharmaceutical components from wastewater using the literature reviews and bibliometric analysis technique from 1970 to 2021 based on the web of science (WoS) database. Various pollutants in water and soil were reviewed, and different methods were introduced to detect pharmaceutical pollutants. The advantages and drawbacks of varying carbon-based materials for sensing and removing pharmaceutical wastes were also introduced. Finally, the available techniques for wastewater treatment, challenges and future perspectives on the recent progress were highlighted. The suggestions in this article will facilitate the development of novel on-site methods for removing emerging pollutants from pharmaceutical effluents and commercial enterprises. Graphical abstract: Image 1 Highlights: A review of carbon nanomaterials for removing pharmaceuticals was conducted. Exponential increase in the (bio)sensors using carbon black was identified. Several analytical methods to detect pharmaceuticals were reviewed. This study offered scientific data to generate new systematic breakthroughs.